2018
DOI: 10.17522/balikesirnef.437735
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Inquiry Based Teaching on Prospective Teachers’ Planning and Practice Processes

Abstract: -The aim of this study is to examine the changes in course planning and the practice processes of prospective science teachers following the in-service trainings they received about open-ended inquiry-based teaching approach (OE-IBTA). With this aim, pre-experimental design with one group post-test was employed.This study was conducted with 12 prospective science teachers in a public university in Turkey. The Course Plan Assessment Rubric and Course Observation Form were developed as data collection instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…In the literature, it is seen that there are studies in which lesson plans related to various teaching approaches are used as data collection tools and rubrics or evaluation forms are developed to evaluate these lesson plans. In this context, it has been determined that there are studies in which lesson plans related to the subject are examined with 5E Model and REACT strategy (Ültay et al, 2018), open-ended inquiry-based teaching approach (Saka et al, 2018), educational game-supported teaching (Gürpınar, 2017), and constructivist approach (Çolak&Yabaş, 2017) and evaluation forms are developed for them. In addition, it has been observed that there are studies examining lesson plans in terms of technology integration (YiğitKoyunkaya&TataroğluTaşdan, 2019) and TPACK (Harris & Hofer, 2009;Harris et al, 2010).…”
Section: Figure 1 the Common Knowledge Construction Modelmentioning
confidence: 99%
“…In the literature, it is seen that there are studies in which lesson plans related to various teaching approaches are used as data collection tools and rubrics or evaluation forms are developed to evaluate these lesson plans. In this context, it has been determined that there are studies in which lesson plans related to the subject are examined with 5E Model and REACT strategy (Ültay et al, 2018), open-ended inquiry-based teaching approach (Saka et al, 2018), educational game-supported teaching (Gürpınar, 2017), and constructivist approach (Çolak&Yabaş, 2017) and evaluation forms are developed for them. In addition, it has been observed that there are studies examining lesson plans in terms of technology integration (YiğitKoyunkaya&TataroğluTaşdan, 2019) and TPACK (Harris & Hofer, 2009;Harris et al, 2010).…”
Section: Figure 1 the Common Knowledge Construction Modelmentioning
confidence: 99%
“…ASDÖ ile ilgili yapılan çalışmalar incelendiğinde, bu çalışmaların ASDÖ'nün etkisi, araştırma sorgulamaya dayalı mesleki gelişim programlarının etkisi ve ASDÖ uygulamaları olarak üç ana konuda gerçekleştiği görülmektedir. Ayrıca ASDÖ'nün etkisine yönelik yapılan çalışmaların öğretmen, öğretmen adayı ve öğrenci grupları üzerinde gerçekleştirildiği de ön plana çıkmaktadır (Saka, 2018;Saka, Akcanca, Kala Aydın ve Sungur Alhan, 2018). ASDÖ'nün etkisine yönelik çalışmalar incelendiğinde, öğretmenlerin ASDÖ'nün etkisi ile kavram bilgilerinin (Lee ve diğ., 2004) ve bili-min doğasına yönelik görüşlerinin (Akerso, Hanson and Cullen, 2007;Parrish, 2017) geliştiği sonucuna varılmıştır.…”
Section: Introductionunclassified